Nanomedicine and versatile therapies for cancer treatment - Shukla A.; Maiti P. (My University, 2025)
The higher prevalence of cancer is related to high rates of mortality and morbidity worldwide. By virtue of the properties of matter at the nanoscale, nanomedicine is proven to be a powerful tool to develop innovative drug carriers with greater efficacies and fewer side effects than conventional therapies. In this review, different nanocarriers for controlled drug release and their routes of administration have been discussed in detail, especially for cancer treatment. Special emphasis has been given on the design of drug delivery vehicles for sustained release and specific application methods for targeted delivery to the affected areas. Different polymeric vehicles designed for the delivery of chemotherapeutics have been discussed, including graft copolymers, liposomes, hydrogels, dendrimers, micelles, and nanoparticles. Furthermore, the effect of dimensional properties on chemotherapy is vividly described. Another integral section of the review focuses on the modes of administration of nanomedicines and emerging therapies, such as photothermal, photodynamic, immunotherapy, chemodynamic, and gas therapy, for cancer treatment. The properties, therapeutic value, advantages, and limitations of these nanomedicines are highlighted, with a focus on their increased performance versus conventional molecular anticancer therapies. © 2022 The Authors. MedComm published by Sichuan International Medical Exchange & Promotion Association (SCIMEA) and John Wiley & Sons Australia, Ltd.